2022
DOI: 10.1080/0886022x.2022.2056054
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota dysbiosis in acute kidney injury: novel insights into mechanisms and promising therapeutic strategies

Abstract: In recent years, the clinical impact of intestinal microbiota–kidney interaction has been emerging. Experimental evidence highlighted a bidirectional evolutionary correlation between intestinal microbiota and kidney diseases. Nonetheless, acute kidney injury (AKI) is still a global public health concern associated with high morbidity, mortality, healthcare costs, and limited efficient therapy. Several studies on the intestinal microbiome have improved the knowledge and treatment of AKI. Therefore, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 116 publications
0
13
0
Order By: Relevance
“…On the other hand, the overgrowth of Anaerosporobacter and Blautia was associated with metabolic dysfunctions in diabetic nephropathy (DN) [ 23 , 24 ]. Interestingly, recent evidence has indicated that intestinal dysbiosis also occurs in acute kidney injury (AKI) [ 25 ]. For instance, Andrianova et al demonstrated by an in vivo study that alterations in the microbiome composition occurred following renal ischemia/reperfusion injury (IRI), and several bacteria including Rothia and Staphylococcus were linked to the high degree of injury [ 26 ].…”
Section: The Gut Microbiome In Health and Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the overgrowth of Anaerosporobacter and Blautia was associated with metabolic dysfunctions in diabetic nephropathy (DN) [ 23 , 24 ]. Interestingly, recent evidence has indicated that intestinal dysbiosis also occurs in acute kidney injury (AKI) [ 25 ]. For instance, Andrianova et al demonstrated by an in vivo study that alterations in the microbiome composition occurred following renal ischemia/reperfusion injury (IRI), and several bacteria including Rothia and Staphylococcus were linked to the high degree of injury [ 26 ].…”
Section: The Gut Microbiome In Health and Kidney Diseasementioning
confidence: 99%
“…Compared with CKD, interest in uremic toxins in AKI was in its infancy in 2009, and the existence of gut–kidney crosstalk in AKI was frequently debated. Today, it is well-established through a variety of experimental animal studies and clinical trials that acute renal damage negatively shapes the microbiota composition [ 25 ]. Importantly, the AKI–microbiota relationship is bidirectional: on the one hand, AKI can cause dysbiosis; on the other hand, the microbial shift influences the severity of the renal injury.…”
Section: The Gut–kidney Axismentioning
confidence: 99%
“…There is now evidence that intestinal dysbiosis is closely linked to AKI, shedding light on kidney-intestine crosstalk in AKI [176][177][178]. Zhu et al [179] demonstrated that the supplementation of Lactobacillus casei Zhang could prevent AKI and impede the progression of CKD by improving intestinal flora, increasing the levels of short chain fatty acids (SCFAs) and nicotinamide in the serum and kid-Yang et al [176] reported that the increase of Enterobacteriaceae and the decrease of Lactobacillus and Ruminococcus were hallmarks of dysbiosis induced by IRI and were related to the decreased levels of SCFAs, intestinal inflammation, and the leaky gut.…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…The gut–kidney axis has been investigated in a number of clinical studies, mostly in CKD [ 108 , 109 , 110 , 111 ]. In septic AKI, impaired gut barrier permeability, with the translocation of bacterial and inflammatory molecules, has also been shown to be associated with the progression of kidney injury and the AKI to CKD transition [ 112 , 113 ]. However, more clinical data are needed to precisely explore the gut–kidney axis and both PUBT generation and accumulation in AKI.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%